PEMBELAJARAN BERBASIS MASALAH TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA - Baiq Fatmawati (UNIVERSITAS HAMZANWADI, 2016)
Natural Sciences are the study of causes and events that occur in nature. Science is believed to be able to train or instill positive attitudes and values in students. Science learning that can be implemented well, will be able to form positive attitudes and values in students as a provision that is needed in overcoming the problems it faces in life. Of course this can be achieved if science learning is seen as a process not just studying the product. The focus of this study is to determine the ability of students in critical thinking through problem based learning on Biology subjects in Selong 1 Public Middle School. This study uses Experiment by using a pre-test and one-group design test post. The population in this study were students of SMP N 1 Selong class VII with a total of 109 students. The research sample was class VII.G which was obtained in a draw. The research instrument was in the form of a test, the test given to students in the form of a critical thinking test about water pollution in the form of essays which numbered 5 questions. The technique of analyzing test data is critical thinking using Gain (d) pre-test and post-test to determine whether there is an increase in the problem of critical thinking skills. The results of data analysis of students' critical thinking skills experienced an increase in score of 0.44, which illustrates an increase with the average value of the pre test students 43.89 to 68.61 in the post test. Thus, it can be said that the application of problem-based learning to biology subjects can improve students' critical thinking skills in Selong 1 Public Middle School.